KARET DAN PEMBATALAN PEMBANGUNAN JALUR KERETA API DI KALIMANTAN SELATAN PADA TAHUN 1930-AN - Tundjung, Tundjung; Noviyanti, Rani (Universitas Negeri Malang, 2021)
Rubber is one of the mainstay products of South Kalimantan at the beginning of the twentieth century. Netherlands Indies Government tried to develop rubber plantations there in order to meet the demand of the world market. The distance between the place of production and the port that is what gave rise to the idea of an entrepreneur building a railway line to transport the rubber from the headwaters to Banjarmasin. As long as this is done through the rubber transport streams, which often encountered obstacles. In the mid 1920 's, the Semarang-Chirebon Stoomtram Maatschappij doing feasibility calculation the construction of railway lines, especially for the transport of the rubber. When planning has been made, at the beginning of the year 1930-ness of the world economic crisis, which promoted trade in rubber. Rubber trade not profitable yet, then the construction of the railway line is not implemented.Karet adalah salah satu produk andalan Kalimantan Selatan pada awal abad kedua puluh. Pemerintah Hindia Belanda berusaha mengembangkan perkebunan karet di sana untuk memenuhi permintaan pasar dunia. Jarak antara tempat produksi dan pelabuhan itulah yang memunculkan ide seorang pengusaha membangun jalur kereta api untuk mengangkut karet dari hulu ke Banjarmasin. Selama ini dilakukan melalui aliran transportasi karet, yang kerap menemui kendala. Pada pertengahan 1920-an, Stoomtram Maatschappij Semarang-Chirebon melakukan perhitungan kelayakan pembangunan jalur kereta api, terutama untuk pengangkutan karet. Ketika perencanaan telah dibuat, pada awal tahun 1930-an krisis ekonomi dunia, yang mempromosikan perdagangan karet. Perdagangan karet belum menguntungkan, maka pembangunan jalur kereta api belum dilaksanakan.